NEGATIVE TRANSFER IN ENGLISH AND IN MACEDONIAN SEEN THROUGH THE TRANSLATION EQUIVALENTS OF THESE TWO LANGUAGES - Vaneva, Marjana (European Scientific Journal, ESJ, 2013)
The notion of negative transfer, which is of crucial importance for understanding negation not only in Macedonian, but also in German, Spanish, French, Russian and many other languages, has attracted the attention of a lot of linguists interested in defining this process. During the second decade of the last century, Jespersen starts talking about the syntactic phenomenon called anticipatory negation, but different authors name this process differently. Fillmore (Fillmore 1963) calls it transposition, Klima (Klima 1964) uses the term absorption, Bolinger (Bolinger 1967) - negative raising, while Robin Lakoff and George Lakoff (R. Lakoff 1969, G. Lakoff 1970) use the string negative transfer. We will look here at the ways in which negation is being carried and transferred from one clause to another, and analyse the semantic differences and implications of this transfer in English and in Macedonian, as the analysis takes into consideration the translation equivalents of these two language structures.